Про особливості несиметричного керування реверсуваннями реактивних елементів у послідовному RLC-колі - Шидловська, Н.А.; Фастова, С.С. (Технічна електродинаміка, 2011)
The processes occurring in an RLC-circuit powered by a sinusoidal voltage source under asymmetric reversal of its reactive element have been investigated. It has been found that processes in a circuit are balancing for a rather long time in comparison with other investigated modes at certain values of time intervals between switching. The carried out numerical experiment in the MATLAB package confirms analytical calculations. The reasons that could generate such process behavior in the system under investigation have been studied.